ON THE ELECTRICAL CONDUCTIVITY STRUCTURE OF THE STABLE CONTINENTAL CRUST - Freund F. (My University, 2003)
A high conductivity zone (HCZ) exists in many places worldwide in the stable mid- to lower continental crust, at the depth of about 20–30 km, but its origin is enigmatic. At this depth range, the temperatures are constrained between 400 and 600 °C and free fluids are believed to have been consumed by retrograde mineral reactions. Many causes for the HCZ have been considered such as residual fluids and brines, partial melting, serpentine or other hydroxyl-bearing minerals in a state of dehydration, but intergranular carbon films have been the most widely accepted explanation. This view is challenged. Electrical conductivity and dielectric polarization measurements on materials as structurally and chemically diverse as laboratory-grown MgO, upper mantle olivine single crystals, and lower crustal anorthosite rock indicate that, in all of them, highly mobile electronic charge carriers are generated in the 450±50–650±50 °C window. These charge carriers are positive holes, e.g. defect electrons in the O 2p-dominated valence band, chemically equivalent to O− in the O2− matrix. They form through dissociation of positive hole pairs, PHP, chemically equivalent to peroxy links, O3X–OO–XO3 (X=Si4+, Al3+ etc.). The PHPs in turn derive from hydroxyl, O3X–OH, that become incorporated into nominally anhydrous minerals whenever they crystallize in H2O-laden igneous or metamorphic environments. Upon cooling, O3X–OH pairs undergo a redox conversion to O3X–OO–XO3 plus H2. Positive hole charge carriers have no problem co-existing with reduced cations under the non-equilibrium conditions that prevail in dry rocks below 600 °C, and they dominate their electrical conductivity in the 400–600 °C temperature range. It is proposed that the HCZ is caused by positive hole charge carriers that are metastably activated in the crust in the 20–30 km depth range.